A STUDY OF ADOPTED BUSINESS TERMS FROM ENGLISH INTO THE UZBEK LANGUAGE - Hasanov Elyorjon Odiljonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Business is an essential part of the country to be developed. So, terms which are used in business should be researched. The article illustrates some terms which are used in business and some special words that are used in some subgroups of business.